Identification of the mcpA and mcpM Genes, Encoding Methyl-Accepting Proteins Involved in Amino Acid and l-Malate Chemotaxis, and Involvement of McpM-Mediated Chemotaxis in Plant Infection by Ralstonia pseudosolanacearum (Formerly Ralstonia solanacearum Phylotypes I and III) - Hida, Akiko (Appl Environ Microbiol, 2015)
Sequence analysis has revealed the presence of 22 putative methyl-accepting chemotaxis protein (mcp) genes in the Ralstonia pseudosolanacearum GMI1000 genome. PCR analysis and DNA sequencing showed that the highly motile R. pseudosolanacearum strain Ps29 possesses homologs of all 22 R. pseudosolanacearum GMI1000 mcp genes. We constructed a complete collection of single mcp gene deletion mutants of R. pseudosolanacearum Ps29 by unmarked gene deletion. Screening of the mutant collection revealed that R. pseudosolanacearum Ps29 mutants of RSp0507 and RSc0606 homologs were defective in chemotaxis to l-malate and amino acids, respectively. RSp0507 and RSc0606 homologs were designated mcpM and mcpA. While wild-type R. pseudosolanacearum strain Ps29 displayed attraction to 16 amino acids, the mcpA mutant showed no response to 12 of these amino acids and decreased responses to 4 amino acids. We constructed mcpA and mcpM deletion mutants of highly virulent R. pseudosolanacearum strain MAFF106611 to investigate the contribution of chemotaxis to l-malate and amino acids to tomato plant infection. Neither single mutant exhibited altered virulence for tomato plants when tested by root dip inoculation assays. In contrast, the mcpM mutant (but not the mcpA mutant) was significantly less infectious than the wild type when tested by a sand soak inoculation assay, which requires bacteria to locate and invade host roots from sand. Thus, McpM-mediated chemotaxis, possibly reflecting chemotaxis to l-malate, facilitates R. pseudosolanacearum motility to tomato roots in sand.